PENGGUNAAN Trichoderma sp. DAN PGPR UNTUK MENGENDALIKAN PENYAKIT PADA TANAMAN STRAWBERRY DI RURUKAN (MAHAWU) - Rante, Caroulus S.; Meray, Elisabet R.M.; Kandowangko, Daisy S.; Ratulangi, Max M.; Dien, Moulwy F.; Sembel, Dantje T. (EUGENIA, 2015)
ABSTRACT Study aims (a) to determine the effectiveness of Trichoderma sp., combination PGPR and Trichoderma sp., and PGPR to the development of diseases that attack strawberry plants, (b) to study the effect of application of Trichoderma sp., combination PGPR and Trichoderma sp. and PGPR for strawberry production.  The experiment was conducted in the village Rurukan (Mahawu), subdistrict Tomohon Timur.  Study lasted from March to August 2013.  Experiments using a randomized block design with 4 treatments, as follows: Treatment A = Trichoderma sp., Treatment B = PGPR, Treatment C = combination of Trichoderma sp. and PGPR, and Treatment D = Control.  The experiment was repeated 4 times.  Data were analyzed using Minitab software ver. 14.  Things that observed the symptoms of disease, number of shoots, roots and heavy weight of strawberries.  The results showed that strawberry plants are not attacked by various diseases. Fungus Verticillium sp. encountered attack strawberry plants with very low intensity.  The average number of shoots ever encountered on the 6.25 shoots PGPR treatment and lowest in the control treatment, ie 2.20 shoots .  The average weight of the heaviest roots found in the PGPR treatment and 68.75 grams of the lowest in the control treatment, which is 13.50 grams.  The average weight of the fruit of the highest found in the 731.25 grams of PGPR treatment and lowest in the control treatment fruit weighing 417.50 grams. Keywords : Trichoderma sp., Verticilium sp., PGPR, Mahawu